Pembentukan Kementerian Investasi/Badan Koordinasi Penanaman Modal Menurut Sistem Hukum Indonesia - Evant Gray Sipayung; Victor Juzuf Sedubun; Vica Jillyan Edsti Saija (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Indonesia as a state of law in every policy taken by the government must be in accordance with the Indonesian legal system, including the formation of the ministry of investment which is regulated in law number 39 of 2008 concerning state ministries and consists of indicators for the formation of ministries.Purposes of the Research: This study aims to identify and analyze the legal basis for the formation of a state ministry and to determine whether the establishment of the investment ministry/investment coordinating agency is in accordance with Law No. 39 of 2008. Methods of the Research: This research uses normative legal research methods, statutory and conceptual approaches to collecting legal materials by means of literature studies and then analyzed.Results of the Research: The legal basis for the formation of state ministries is the 1945 Constitution of the Republic of Indonesia, Law 39 of 2008 and the issuance of Presidential Decree No. 72/P of 2021 and Presidential Decree No. 63 of 2021 and the establishment of the investment ministry does not consider indicators of efficiency and effectiveness.